The Analytic Network Process of Indonesia’s Bioethanol: Future Direction of Competitive Strategy and Policy - Indahsari, Gita K.; Daryanto, Arief; Said, E. Gumbira; Wibowo, Rudi (Analisis Kebijakan Pertanian, 2016)
Increased consumption of fossil fuel has been an escalating debate related to its limited deposit and global warming issue. Recently, the oil price tends to rise. Bioethanol has been considered as an alternative substitute for fossil fuel because it is renewable and environmentally friendly. Indonesia plans to develop the bioethanol industry since 2006 but until 2011 it has not been realized yet besides its well planned blue-print and target.This study is aimed to determine factors affecting the competitiveness of the bioethanol industry as well as to select a competitive strategy. Data collection was conducted from April to December 2010 in six cities. Analytic Network Process (ANP) was used as a method in this study. There were four categories, namely problems, alternative of solutions, policies, and strategies. Results from the development of bioethanol competitive industry framework suggested that: (1) sugarcane is considered the most potential resource for bioethanol raw material, (2) government’s lack of coordination is the main problem for developing competitiveness, and (3) a new bioethanol blueprint policy with a through stakeholder strategy to increase competitiveness of the bioethanol industry in Indonesia is needed.